Nomograms for Predicting Overall Survival and Cancer-Specific Survival of Patients With Renal Cell Carcinoma and Venous Tumor Thrombus: A Population-Based Study - Yang, Lin; Fu, Bin (Frontiers in Surgery, 2022)
Abstract Background: To provide better prognostic information for patients with renal cell carcinoma (RCC) combined with venous tumor thrombus (VTT). In turn, guide patients' families and doctors to formulate plans for follow-up treatment and follow-up. We developed nomograms to predict cancer-specific survival (CSS) and overall survival (OS). methods: A total of 2961 cases were included in this study. Through univariate and multivariate Cox proportional hazard regression analysis, independent risk factors affecting CSS and OS were screened out, and then a nomogram was drawn based on the screened variables. Results: Independent risk factors affecting CSS include: tumor size (HR=1.05), histology (HR=1.75), grade (HR=1.94), N staging (HR=2.06), and M staging (HR=2.87). The median survival time for CSS was 106 months. Independent risk factors for OS include age (HR=1.60), tumor size (HR=1.04), histology (HR=1.60), grade (HR=1.68), N staging (HR-1.99), M staging (HR=2.45). The median survival time for OS is 67 months. Conclusions: The nomogram based on independent risk factors affecting CSS and OS can well predict the prognosis of renal cell carcinoma with venous tumor thrombus.